Magazine «Parochial School» as a Historical and Pedagogical Source for the Study of Pedagogical Parish Schools ( end of the 19th century – beginning of the 20th century) - Svitlana Brychok (Pedagogical Discourse, 2013)
In article we analyze the magazine «Parochial school» as one of the important sources of historical and pedagogical research. The author considers features of pedagogical ideas of the period under research, traces the dynamics of educational processes, their focus, and role of the educational theory and educational research priorities of the end of the 19th century – beginning of the 20th century. On the basis of the magazine materials «Parochial school» we concluded that the parish schools were an important element of public primary education, they worked by the general program and had a very clear system of teaching. Magazine of the Holy Synod «Pparochial school» helped to shape teaching skills of the parish school teachers, was a kind of teaching aids, platform for the exchange of experience of creative teachers.